The 'Lay folks' catechism' - an edition - Greig, Pamela L.C. (2018)
This thesis presents the first critical edition of the Lay Folks’ Catechism using the previously unpublished Oxford, Bodleian MS Don.c.13 as the base text. The list of extant witnesses is revised and includes the newly discovered Chetham Library fragment. The edition presents detailed manuscript descriptions, variants from all 26 witnesses, notes on the text and a comprehensive glossary. The introduction considers the roles of Archbishop Thoresby and the Benedictine John de Gaitrik in commissioning and composing the Catechism, and its sources and orthodoxy are confirmed. Scribal presentation of the text as verse or prose is re-examined in conjunction with Gaitrik’s use of punctuation and various literary devices, and a new conclusion reached concerning the text’s construction. The Catechism’s distribution and circulation, its effectiveness as a didactic text, and the transition from northern clergy to non-secular ownership are discussed. The edition establishes the importance of the Catechism in late medieval vernacular pastoralia aimed at a pious lay audience